EXPORT PERFORMANCE OF INDONESIAN BLACK PEPPER IN THE UNITED STATES MARKET - Tarigan, Anita Carolin Aprilia; Suharno, Suharno; Harmini, Harmini (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2024)
Indonesia pepper, contributing 11% of the U.S. market, is below Vietnam as a significant supplier and is followed by Brazil. Based on the growth rate of Indonesian pepper exports to the U.S. market, Indonesia is second after Vietnam. Indonesian pepper exports to the American market have limitations, and competition exists between the countries exporting pepper. The research used the export of a sort of whole black pepper. This study aims to determine Indonesian black pepper's competitiveness and demand position in the U.S. market. The performance of Indonesia's black pepper exports to the U.S. market was analyzed using the revealed comparative advantage (RCA) method, export product dynamics (EPD), and the almost ideal demand system (AIDS) method. The dependent variable is the share of Indonesia, Vietnam, Brazil, and India, and the independent variable is the price of pepper from the countries. The analysis results show that black pepper has comparative and competitive competitiveness. Indonesian black pepper has the highest expenditure elasticity, elastic price elasticity, and cross elasticity; it is a substitute for Vietnam and complementary to Brazil and India. Indonesian black pepper has good export performance and a high demand for imports, so Indonesia has the potential to increase exports by increasing the export volume of quality pepper at competitive prices, according to what the U.S. market wants.